PENGERINGAN KONSENTRAT PROTEIN DARI DAUN TURI PADA SUHU RENDAH DENGAN FLUIDIZED BED DRIER - Yenni Pintauli Pasaribu (AGRICOLA, 2012)
Turi leaves as a cheap protein source can be converted into protein concentrates for feed livestock industrial raw material. The analysis results for the leaf indicate that turi has moisture content of 83-84%, crude protein content 4.1-4.8%, crude fibre 2,5-2,9%, and ash levels 1,3-1,5%. Whereas the analysis results for turi leaves concentrates has 40,15% protein, 1,09% ash, and 0,74% crude fibre. The method for making turi leaves concentrates consist by three processes i.e., coagulation, extraction and drying results. The extraction is done by using a blender by comparison raw materials:solvent of 1:3 and extraction for 3 minutes. Coagulation process is done by the addition of 1 N HCl to pH 3.5 and warming obtained at a temperature of 70oC for 10 minutes. The drying is done with fluidized bed drier at low temperatures, i.e. 40-57oC.  The variable learned is the speed of air drying and humidity. Mathematical model that was compiled can be used to predict drying process quite well. The relationship between the coefficient of effective difusivity (De) with the mass transfer coefficient (Ky) can be expressed by dimensionless number Sh = 2, 6292.10-11 Re6.6387 with corrected average of 7,5293%. The equation can be used to determine the value of Ky that could be used to predict drying process for turi leaves protein concentrates with fluidized bed drier on the other conditions. The results of the analysis show that protein concentrates made from turi leaves has 40,15% protein, ash levels 1,09%, and crude fibre 0,74%.